Phonon Focusing and Phonon Transport In Single-Crystal Nanostructures - Kuleyev, Igor Gaynitdinovich (Texts and monographs in theoretical physics., 2020)
The monograph is devoted to the investigation of physical processes that govern the phonon transport in bulk and nanoscale single-crystal samples of cubic symmetry. Special emphasis is given to the study of phonon focusing in cubic crystals and its influence on the boundary scattering and lattice thermal conductivity of bulk materials and nanostructures.